Television Cities : Paris, London, Baltimore - Brunsdon, Charlotte (Book collections on Project MUSE., 2018)
In Television Cities Charlotte Brunsdon traces television's representations of metropolitan spaces to show how they reflect the medium's history and evolution, thereby challenging the prevalent assumptions about television as quintessentially suburban. Brunsdon shows how the BBC's presentation of 1960s Paris in the detective series Maigret signals British culture's engagement with twentieth-century modernity and continental Europe, while various portrayals of London--ranging from Dickens adaptations to the 1950s nostalgia of Call the Midwife--demonstrate Britain's complicated transition from Victorian metropole to postcolonial social democracy. Finally, an analysis of The Wire's acclaimed examination of Baltimore, marks the profound shifts in the ways television is now made and consumed. Illuminating the myriad factors that make television cities, Brunsdon complicates our understanding of how television shapes perceptions of urban spaces, both familiar and unknown.